2020
DOI: 10.7554/elife.50371
|View full text |Cite
|
Sign up to set email alerts
|

Temporal cascade of frontal, motor and muscle processes underlying human action-stopping

Abstract: Action-stopping is a canonical executive function thought to involve top-down control over the motor system. Here we aimed to validate this stopping system using high temporal resolution methods in humans. We show that, following the requirement to stop, there was an increase of right frontal beta (~13 to 30 Hz) at ~120 ms, likely a proxy of right inferior frontal gyrus; then, at 140 ms, there was a broad skeletomotor suppression, likely reflecting the impact of the subthalamic nucleus on basal ganglia output;… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
161
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(207 citation statements)
references
References 89 publications
23
161
1
Order By: Relevance
“…Consistent with recent studies, this parametric estimation technique resulted in an attenuation of SSRT compared to the traditional nonparametric integration method (Band et al, 2003;Jana et al, 2020;Matzke, Love, et al, 2017;Skippen et al, 2019;Weigard et al, 2019). Importantly, SSRT int was only moderately correlated with SSRT EXG3 , but was strongly associated with trigger failure.…”
Section: Nonparametric Versus Parametric Estimates Of Ssrtsupporting
confidence: 81%
See 3 more Smart Citations
“…Consistent with recent studies, this parametric estimation technique resulted in an attenuation of SSRT compared to the traditional nonparametric integration method (Band et al, 2003;Jana et al, 2020;Matzke, Love, et al, 2017;Skippen et al, 2019;Weigard et al, 2019). Importantly, SSRT int was only moderately correlated with SSRT EXG3 , but was strongly associated with trigger failure.…”
Section: Nonparametric Versus Parametric Estimates Of Ssrtsupporting
confidence: 81%
“…The notion of an automatic response inhibition process is supported by both the fast estimates of SSRT (≈130 ms; see also Matzke, Hughes, et al, 2017;Skippen et al, 2019) and by motor evoked potential studies that suggest the inhibition processes occurs around 140 ms (Coxon, Stinear, & Byblow, 2006;Jana et al, 2020;Raud & Huster, 2017;Waldvogel et al, 2000;Wilcoxon, Nadolski, Samarut, Chassande, & Redei, 2007). In fact, a recent multi-modal study by Jana et al (2020) showed that the cascade of processing that occurs during the stop-signal task suppresses muscle activity within 160 ms after a visual stop-signal onset. As the registration of auditory signals occurs around 30 ms earlier than visual signals (Jain, Bansal, Kumar, & Singh, 2015;Ramautar, Kok, et al, 2006), the 130 ms estimate of SSRT found here is consistent with the fast inhibition process described by Jana et al (2020).…”
Section: The Stop-n1-an Index Of Automatic Inhibition Processes?mentioning
confidence: 94%
See 2 more Smart Citations
“…In fact, studies have shown that both the peak and onset latency of the P3 might correlate with the SSRT [13][14][15][16] , suggesting that P3 latency measures could be potential neural markers of inhibitory capability. In addition to this, studies have found that the effects of inhibitory control can be measured by electromyographic (EMG) activity at response effector muscles in successful stop trials 4,[17][18][19] . While the onset of this so-called partial response EMG (prEMG) reflects the response to the preceding go stimuli, the point for the prEMG decline (i.e.…”
mentioning
confidence: 99%